Design, Visual Communication and Branding. - Raposo, Daniel (Cambridge Scholars Publishing, 2022)
This book highlights how digital communication has brought about changes in branding, namely in design, the media, communication languages, the relationship with audiences, experience design, behaviour, culture, and brand management mechanisms. On the other hand, as it argues, artificial intelligence has opened the door to other ways of dealing with big data and communicating with mass audiences, through the customization of messages or a one-to-one logic. Overall, the book shows that the intersections between digital communication and artificial intelligence point towards a new reality in bra.